Synthesis and antikinetoplastid activity of a series of N,N×-substituted diamines - Caminos, Andrea P. (2012)
A series of 25 N,N×-substituted diamines were prepared by controlled reductive amination of free aliphatic diamines with different substituted benzaldehydes. The library was screened in vitro for antiparasitic activity on the causative agents of human African trypanosomiasis, Chagas´ disease and visceral leishmaniasis. The most potent compounds were derived from a subset of diamines that contained a 4-OBn substitution, having a 50% parasite growth inhibition in the submicromolar (against Trypanosoma cruzi) or nanomolar (against Trypanosoma brucei and Leishmania donovani) range. We conclude that members of this series of N,N×-substituted diamines provide new lead structures that have potential to treat trypanosomal and leishmanial infections. © 2011 Elsevier Ltd. All rights reserved.